Recurrent malignant fibrous histiocytoma of the forearm: A rare soft tissue sarcoma: Recurrent malignant fibrous histiocytoma - Gökçe, Kağan; Doğan , Demet; Yazıcı , Merve; Karadayı , Ayşe Nimet; Midi , Ahmet (Journal of Surgery and Medicine, 2024)
Malignant fibrous histiocytoma (MFH), while rare, is the most prevalent soft tissue sarcoma (STS) found in extremities. Its prognosis hinges on factors such as tumor size, invasion depth, and differentiation degree. For MFH and all STSs, wide surgical resection is the gold standard treatment method. In this study, a 48-year-old woman, initially diagnosed with lipoma and with a mass excised from her right forearm, later exhibited recurring MFH masses in the same location. Superficial tissue ultrasonography identified malignant soft tissue tumors in the lesion area. Positron emission tomography was used to stage the tumor preoperatively, revealing fluorodeoxyglucose uptake in the repeating lesions. Right forearm magnetic resonance imaging confirmed the malignant lesions. Post imaging, the patient underwent wide surgical excision, eliminating the fascia. Regular follow-up revealed no recurrence or metastasis at 6 months and 1 year. Excisions frequently occur without radiological imaging, based only on a preliminary lipoma or sebaceous cyst diagnosis. However, excisions should follow radiological imaging, particularly when soft tissue tumors beneath the skin appear benign.